INVESTIGASI EMPAT FAKTOR KONTINGENSI SEBAGAI VARIABEL MODERATING TERHADAP PARTISIPASI PEMAKAI DAN KEPUASAN PEMAKAI DALAM PENGEMBANGAN SISTEM INFORMASI - Meirina Cherta Kusumastuti; Soni Agus Iwandi (Universitas Hayam Wuruk Perbanas, 2012)
User participation in information system development is an important factor affecting thesuccess of a system. User satisfaction is one of the successful developments of informationsystems. This study aims to provide empirical evidence about the effect of user participationon user satisfaction in the development of information systems and prove that the complexityof the task, system complexity, user influence and user-developer communicationmoderate the influence of user participation on user satisfaction in information systemsdevelopment. Sampling technique used judgment sampling. The samples were staffs whowere involved in the development of information systems at the national bank in the regionof Surabaya and consisting of 75 respondents. The method that used in this study was asimple linear regression to test the effect of participation in the use of user satisfaction ininformation systems development, while the absolute value of the difference test to examinethe effect of moderating variables. The results showed that the participation of users significantlyaffect user satisfaction in information systems development, the influence of usersand complexity of the task moderate the influence of user participation on user satisfactionin information system development, system complexity and user-developer communicationmoderate the influence of user participation on user satisfaction in development of informationsystems.